Diodorus 18. 39.1–7 and Antipatros’s Settlement at Triparadeisos - Landucci Gattinoni, Franca (Anabasis. Studia Classica et Orientalia, 2011)
Books 18–20 in Diodorus Siculus’ Library provide a continuous record of events from Alexander the Great’s death to the eve of the Battle of Ipsos at the end of the archon year of 302/1. Book 18 deals with the period between 323 and 318 and is entirely devoted to events in Greece and in the East; there is no reference to Sicilian and Roman affairs. At 18. 39.1–7, Diodorus narrates of the conference at Triparadeisos, an unknown Syrian town: after the Babylon Settlement in June 323, Antipatros supervised another distribution of satrapies. There were few surprises: the murderers of Perdikkas were rewarded; the war against the Perdikkan forces in Asia Minor was assigned to Antigonos; Seleukos received Babylonia, the nucleus of his future kingdom. At 18. 39.7, Diodorus concludes the chapter portraying Antipatros crossing the Hellespont in order to return to Macedonia with the kings. He says nothing about Antipatros’s deeds on the way from Triparadeisos to the Hellespont: about these deeds we are informed only by Arr. Succ. 1.40–45. Therefore, we can suppose Diodorus (or, better, his source) actually ‘effaced’ Antipatros’s march across Asia Minor by focusing only on Antipatros’s return to Macedonia.